Response to engineer's letter Ref. BRACU-NCP-2018 25A & 26A - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding response to engineer's letter Ref. BRACU-NCP-2018 25A & 26A of BRACU new campus development project.